Measuring Revisit Intention of Domestic Tourists in Langkawi UNESCO Global Geopark, Malaysia: A Road to Sustainable Tourism - YUSOF, Mohd Fadil Mohd; KAMARUDIN, Lina Munirah; PATWARY, Ataul Karim; MOHAMED, Ahmad Edwin (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
Domestic tourism in Malaysia has contributed significantly to the country's economy and made a sustainable impact on the tourism industry. Langkawi is one of the most visited tourists' attractions in Malaysia which is well-known for island tourism and Geotourism. This study explores the relationship of tourists' motivation, destination brand engagement and domestic tourists' revisit intention in Langkawi UNESCO Global Geopark, Malaysia. The study also examined the mediating role of destination brand management and destination trust between tourists motivation and revisit intention. This study used a quantitative approach to explore the relationships among dependent, independent and intervening variables. A total of 300 questionnaires were distributed, and 212 usable questionnaires returned and utilised for further analysis. For analysis purpose, the researchers decided to utilise SPSS version 25.0 for descriptive statistics and PLS-SEM version 3 for inferential analysis. The results found that tourists' motivation significantly influences destination brand engagement and destination trust for a direct relationship. Results also found that destination brand engagement and destination trust significantly affect tourists' revisit intention in Geopark Langkawi, Malaysia.